Crapemyrtle Pruning - Gary W. Knox; Edward F. Gilman (EDIS)
ENH1138, a 5-page illustrated fact sheet by Gary W. Knox and Edward F. Gilman, addresses this controversial aspect of crapemyrtle maintenance, providing recommendations based on UF/IFAS research clarifying the effects of various crapemyrtle pruning practices. Includes references. Published by the UF Department of Environmental Horticulture, September 2009.